Why Should We Care about Care? : The Role of Childcare and Eldercare in Bosnia and Herzegovina - Levin, Victoria (World Bank, Washington, DC, 2018)
Despite significant progress in closing the gender gap in education, there is a significant disparity between male and female labor participation rates in Bosnia and Herzegovina (BiH). Among men aged 15 to 64 years, 65.7 percent participate in the labor force compared to only 41 percent of females in the same age group. It is estimated that BiH forgoes around 16 percent of gross national income due to gender disparities in labor force participation. The conflicting demand of women's time for care and work activities represents a fundamental barrier to economic participation and generates a vicious circle of low labor market attachment and prominence of the care provider role that leads to increased vulnerability and gender-based inequalities.